The twofold transition: Framing digital innovations and incumbents' value propositions for sustainability - Karolina Bähr; Alexander Fliaster (Business Strategy and the Environment, 2022)
Although digital technology offers many sustainable business model opportunities, they are not always exploited. We argue that the framing of technology is still rarely considered a cognitive antecedent of business models for sustainability, despite that it offers insightful explanations, connecting technology's sustainability potential to its business model implementations. We conduct a qualitative multicase study of virtual power plants, adopted by seven incumbent companies in the German energy sector, and explore how they frame innovative digital technology, as well as how it affects their value propositions and the energy transition. Our research reveals several value proposition differences between two company groups. The first generates a single-focused technological frame, concentrating on economic value. The second constructs a twofold digital and sustainable technological frame, resulting in additional socioenvironmental value components. Overall, companies that create a twofold frame operate as renewable energy enablers or system supporters and contribute to the energy transition.
Keywords: 650; business models for sustainability; digital innovation; energy; sustainability; technological frame; value proposition